EFFECTIVENESS OF THE PEDAGOGICAL MODEL OF FORMING IDEOLOGICAL IMMUNITY IN STUDENTS: STATISTICAL ANALYSIS OF EXPERIMENTAL WORK (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
The article presents the results of an experimental study testing the effectiveness of a three-tier model of pedagogical prevention of religious extremism in secondary schools. The study was conducted during the 2024–2026 academic years in four schools and involved 390 participants (240 pupils of grades 8–9, 60 teachers, 90 parents). The baseline stage showed that 68,3 % of pupils do not verify the source of online information, while the teacher is the least consulted source for questions of religious content (9,6 %). After the formative stage, the high level of ideological immunity in the experimental group rose by 22,5 percentage points and the low level fell by 35,0. The results were confirmed by the chi-square test (χ² = 20,36; df = 2) and Student’s t-test (t = 10,42; df = 238) at p < 0,001, with an effect size (Cohen’s d) of 1,34.